A giant spinal arterial aneurysm in a child presenting as quadriparesis. (20th August 2013) - Santana-Ramírez, Adrian; Farias-Serratos, Felipe; Garzon-Muvdi, Tomas; Quiñones-Hinojosa, Alfredo
Abstract : A giant spinal aneurysm from anterior spinal artery not associated with arteriovenous (AV) malformations is unusual and no such cases have been reported in children. Few cases have been described as part of AV malformation complex and coarctation of the aorta. We report a case of anterior spinal aneurysm in a 1-year-old girl causing a subarachnoid haemorrhage and a cervical cord lesion. The diagnosis was confirmed with a multislice CT angiography. A microsurgical decompression was performed and excision of aneurysm was unsuccessful but neurological deficits were improved. No further approach was accepted by the parents. The mechanism for the development of spinal isolated aneurysms is not clear; it can be related to congenital vessel abnormalities and genetic origin. The multislice CT angiography is a very useful method to demonstrate the features of this entity. Previous reports of isolated spinal aneurysm are reviewed.